Lawsuits for the recovery of possession as actions that civilly interrupt the usucapion. Criticism of the dominant stance in the case law - Villegas Valenzuela, José Manuel (2023)
In this article, the author critically studies the main stance in Peru’s case law, in relation to the usucapion which sustains that the initiation of lawsuits and the submittal of letters recorded by a civil law notary public to the person incurring in cases of usucapion are actions that affect the undisturbed and full possession of the property. To this effect, the author makes an indepth analysis of some of the interpretations proposed on the subject. Subsequently, he concludes that such hypotheses do not affect the undisturbed and full possession of the property and that only those lawsuits designed to order the recovery of the property qualify as actions that interrupt the usucapion (adverse possession).